2020
DOI: 10.1038/s41598-020-68179-9
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterial biofilm formation is a multifactorial adaptive phenomenon in response to bile exposure

Abstract: In the current study, we show that biofilm formation by various strains and species belonging to Bifidobacterium, a genus that includes gut commensals with reported health-promoting activities, is induced by high concentrations of bile (0.5% (w/v) or higher) and individual bile salts (20 mM or higher), rather than by acid or osmotic stress. The transcriptomic response of a bifidobacterial prototype Bifidobacterium breve UCC2003 to such high bile concentrations was investigated and a random transposon bank of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Although in silico investigations aimed at predicting the presence of the lux S gene in bifidobacteria has been limited to only a small number of species, its conservation in all analysed genomes suggests the possible presence of such a gene in all bifidobacterial species [8] , [142] , [143] . Despite the as yet incomplete characterization of this cell density-dependent regulatory mechanism within the genus Bifidobacterium , bifidobacterial AI-2 production seems to be involved in biofilm formation, suggesting that AI-2 plays a crucial role in influencing the colonization of these symbiotic microorganisms in the gut ecosystem [96] , [142] . This hypothesis was further corroborated by the observation that a B. breve UCC2003 lux S insertion mutant strain is much more sensitive to multiple iron chelators, is not able to colonize the murine GIT and was shown to confer less protection against a pathogen infection in Caenorhabditis elegans [143] .…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in silico investigations aimed at predicting the presence of the lux S gene in bifidobacteria has been limited to only a small number of species, its conservation in all analysed genomes suggests the possible presence of such a gene in all bifidobacterial species [8] , [142] , [143] . Despite the as yet incomplete characterization of this cell density-dependent regulatory mechanism within the genus Bifidobacterium , bifidobacterial AI-2 production seems to be involved in biofilm formation, suggesting that AI-2 plays a crucial role in influencing the colonization of these symbiotic microorganisms in the gut ecosystem [96] , [142] . This hypothesis was further corroborated by the observation that a B. breve UCC2003 lux S insertion mutant strain is much more sensitive to multiple iron chelators, is not able to colonize the murine GIT and was shown to confer less protection against a pathogen infection in Caenorhabditis elegans [143] .…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
“…Specifically, bile salt hydrolases confer protection by catalysing the de-conjugation of glycine and taurine from bile salts generating unconjugated acids that can be metabolized by other intestinal bacteria [94] , [95] . In addition, biofilm formation has been proposed as a crucial adaptive strategy in response to bile stress relying on a multi-factorial process involving exopolysaccharide (EPS) production as well as protein and extracellular DNA release, as observed in the bifidobacterial prototype B. breve UCC2003 [96] .…”
Section: Introductionmentioning
confidence: 99%
“…All Bifidobacterium strains sequenced harbor luxS genes, which are involved in the production of the classic QS signaling molecule autoinducer-2 (AI-2) [ 22 , 23 , 24 ], yet no AI-2 receptor has been reported in this genus [ 25 ]. Despite a vast amount of research on biofilm formation [ 26 ], its mechanism has not yet been fully elucidated in many bacterial species, and it is especially true for Bifidobacterium species [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies tested purified bile acids, rather than bile extract, and showed that all bacteria did not induce biofilm in response to the same bile acid. For instance, C. difficile reacted to deoxycholate (Dubois et al, 2019), B. breve to conjugated bile acids (taurocholate, glycocholate, taurodeoxycholate, glycodeoxycholate) (Kelly et al, 2020), and Lactobacillus to taurocholate (Ambalam et al, 2012). Conversely, taurine-conjugated bile acids disperse biofilms of V. cholerae or P. aeruginosa (Hay and Zhu, 2015; Sanchez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%